P.C.A. : Projecte, Concepte & Actionen - Aue, Walter (Kôln : Verlag M. DuMont Schauberg Köln, 1971)
Albert, Dietrich ; Altorjay, Gabor ; Andersen, Eric ; Arias-Misson, Alain ; Arnatt, Keith ; Artmann, H.C. ; Aue, Walter ; Baxter, Iain ; Becher, Bernd & Hilla ; Becker, Jürgen ; Beuys, Joseph ; Bienek, Horst ; Bochner, Mel ; Boezem, Marinus ; Böhmler, Claus ; Bollinger, Bill ; Brecht & MacDiarmid ; Brecht, George ; Brinkmann, Rolf Dieter ; Brock, Bazon ; Brouwn, Stanley ; Brunner, Edy ; Brus, Günter ; Burgy, Donald ; Burkhardt, Linde ; Buthe, Michael ; Byars, James Lee ; Calzolari, Pierpaolo ; Carlini, Alessandro ; Chotjewitz, Renate & Peter O. ; Christiansen, Henning ; Christo ; Cintoli, Claudio ; Claus, Jürgen ; Cotton, Paul ; Darboven, Hanne ; Derschau, Krystof ; Dibbets, Jan ; Dietrich, HJ ; Distel, Herbert ; de Dominicis, Gino ; Dressler, Otto ; van Elk, Ger ; Ernst, Wolfgang ; Esser, Manfred ; Filliou, Robert ; Fulton, Hamish ; Geldmacher, Klaus ; Gendolla ; Gerz, Jochen ; Geuer, Johannes ; Giese, Rainer ; Gilbert & George ; Glasmacher, Dieter ; Gosewitz, Ludwig ; Graham, Dan ; Gräsel, Friedrich ; Graubner, Gotthard ; Groh, Klaus ; Guben, Gunther ; Haacke, Hans ; Hagen, Erwin ; Handke, Peter ; Hansen, Al ; Harvan, Gerhard ; Haus-Rucker-Co ; Hendricks, Bici ; Hendricks, Geoff ; Herms, Uwe ; Hesterberg, Thomas ; Heydemann, Jorg ; Higgins, Dick ; Highstein, Jene ; Hingsmartin ; Hödicke, Karl Horst ; Hoffmann, Gerd E. ; Höke, Bernhard ; Hollein, Hans ; Immendorff, Jörg ; Jelinek, Elfriede ; Kagel, Mauricio ; Kahlen, Wolf ; Kaprow, Allan ; Kawara, On ; Kemner, Felix ; Kiënder, Ursula & Ed ; Kircher, Git ; Knauer, Roland ; Knoebel, Imi ; Koepcke, Arthur ; Körbel, Alfons ; Kosuth, Joseph ; Kounellis, Jannis ; Kozlow, Christine ; Kren, Kurt ; Kreutz, Nikolaus ; Kroutvor, Josef ; Kudo, Tetsumi ; Lamelas, David ; Lobach, Bernd ; Lüthi, Urs ; etc.
Gekopieerde versie
Duits
boek